2022
DOI: 10.1021/acs.jafc.2c02949
|View full text |Cite
|
Sign up to set email alerts
|

Promoted Formation of Pyrazines and Sulfur-Containing Volatile Compounds through Interaction of Extra-Added Glutathione or Its Constituent Amino Acids and Secondary Products of Thermally Degraded N-(1-Deoxy-d-ribulos-1-yl)-Glutathione

Abstract: An Amadori rearrangement product (ARP) derived from ribose (Rib) and glutathione (GSH) was prepared and identified as N-(1-deoxy-D-ribulos-1-yl)-glutathione by ultraperformance liquid chromatography−tandem mass spectrometry and NMR. Thermal treatment of the ARP aqueous solution was conducted, and a relatively high temperature was found to accelerate the degradation of the ARP. The concentration of furans formed at 120 °C was more than 6.39 times that at 100 °C, and especially, the high temperature favored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Specifically, the amount of methylpyrazine and 2,5-dimethylpyrazine produced in the Thr-ARP/threonine model was 2.54 times and 3.81 times that in the Thr-ARP model at the 240th min, respectively. Therefore, it could be concluded that exogenous threonine promoted the formation of pyrazines in the Thr-ARP model in terms of both concentration and species, which was consistent with the reported research. , However, the role exogenous threonine played in the formation of pyrazines in the Thr-ARP model still remained unclear. Thus, the pathway of the Maillard reaction of Thr-ARP with the involvement of free threonine was further researched by using 15 N-labeled threonine.…”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, the amount of methylpyrazine and 2,5-dimethylpyrazine produced in the Thr-ARP/threonine model was 2.54 times and 3.81 times that in the Thr-ARP model at the 240th min, respectively. Therefore, it could be concluded that exogenous threonine promoted the formation of pyrazines in the Thr-ARP model in terms of both concentration and species, which was consistent with the reported research. , However, the role exogenous threonine played in the formation of pyrazines in the Thr-ARP model still remained unclear. Thus, the pathway of the Maillard reaction of Thr-ARP with the involvement of free threonine was further researched by using 15 N-labeled threonine.…”
Section: Results and Discussionsupporting
confidence: 89%
“…The exogenous glutamic acid involved in the degradation of glutamic acid–galactose ARP obviously improved the yield of pyrazines . Similar phenomena also occurred in the model of glutathione–ribose ARP, as well as in the ARP derived from glucose and l -alanyl- l -glutamine. , …”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Pyrazines and methional were identified by comparison of their mass spectra with the mass spectral database (NIST 17) and the calculated linear retention indices (RIs) relative to n-alkanes (C 7 −C 30 ) and authentic compounds. The quantitation of pyrazines and methional was performed, according to the method of Feng et al 18 The internal standard (5 μL 1,2-dichlorobenzene, 0.018 mg/mL) was added to different concentrations of mixed standard compounds, and the ratio of peak areas of standard compounds relative to that of 1,2dichlorobenzene was used to establish the external calibration curves (Table S2). The x and y represented the concentration (mg/L) of the standard compound and the ratio of the peak area of the respective standard compound to that of the internal standard, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The retention indices were calculated according to the retention time of n-alkanes (C 7 −C 30 ) analyzed under the same conditions and compared with the Kovats indices acquired from the NIST database. The quantitative analysis of pyrazines and furans performed was according to the method proposed by Feng et al 22 Statistical Analysis. The results were analyzed by SPSS 23.0, and p < 0.05 was considered as significant.…”
Section: Analysis Of Volatile Compounds By Hs−spme/gc−msmentioning
confidence: 99%